Analysis of a self-supporting shell concrete roof with nonlinear coupled evolutive material parameters - Landry Djopkop Kouanang; Merlin Bodol Momha; Daniel Ambassa Zoa; Jean Chills Amba; Joseph Nkongho Anyi; Robert Nzengwa (PLoS ONE, 2025)
In many concrete-design civil engineering constructions, structural analyses are performed through finite element methods on an ideal equivalent elastic homogeneous material. However, in some cases, the evolution of these structures is impacted by delay effects (creep, shrinkage, etc.) and hydration, which sometimes also create structural damage. In this work, we propose a design method that includes the thermochemical and hydromechanical (TCHM) behaviour of concrete materials. An experimental design was carried out on concrete samples cast under laboratory conditions to monitor strain. A finite element method was subsequently used to simulate the behaviour of the sample under drying conditions. The gradient development linked by a nonuniform moisture distribution in the thickness was established by solving the nonlinear partial differential drying equation with Mensi’s diffusion law. The stress and displacement analysis was modelled by sixnodes (MT6) based on strain approximation with shell theory. The results indicated that considering the delayed effects associated with the mechanical change on the thickness variation produces an effect identical to that which would have been produced by an individual mechanical loading worth 183 times the value of the mechanical loading considered. The deformation was calculated using the finite element method. This method was successfully applied to a self-supporting concrete roof.